Application of Fixed-Wing UAVs to Develop Digital Terrain Model on Coastal Peatland Bengkalis Island - Hendra Saputra; Willy Okcandra; Sigit Sutikno; Muhammad Zainuddin Lubis (Journal of Applied Geospatial Information, 2023)
Destructive abrasion is currently occurring in Teluk Papal Village. The coast of Teluk Papal Village has a humus soil structure with soil conditions with a type of peat that is relatively easy to decompose. The cause is along the coast because of the absence of coastal protection plants (mangroves). To prevent the increasing abrasion rate, a comprehensive plan is needed by involving relevant stakeholders in both short and long-term planning. One of the efforts in controlling the abrasion rate is the construction of breakwater buildings. Before the construction is carried out, a study is needed to support the breakwater construction. One of the supports is to make a topographic or contour map. The field data acquisition process uses Unmanned Aerial Vehicle (UAV) technology. This data processing technique uses photogrammetric data processing techniques with the stages of flight path planning, measurement of Ground Control Point (GCP), and Benchmark points, which are then tied to BIG's CORS points to produce higher control point accuracy, Dense Cloud Point to create Digital Elevation Model (DEM) or Digital Terrain Model (DTM), and orthophoto embellishment. Furthermore, horizontal and vertical position accuracy tests were conducted using the calculation method issued by BIG regulation No. 15/2014 to provide information on how far the accuracy of the resulting map is. The results of the Digital Terrain Model (DTM) and orthophoto data accuracy test research based on the results of the accuracy test obtained a LE90 value of 0.6757 meters, then for the CE90 value of 0.1543 meters so that it meets the map requirements at a scale of 1:2500 at class 1 horizontal accuracy and class 2 vertical accuracy. Keywords: Digital Elevation Model, Ground Control Point, Orthophoto, Topography, Unmanned Aerial Vehicle